JISMONIY MADANIYAT SHAKLLANISHIDA SHAXSIY SOG'LIQNI SAQLASHNING TA’RKIBIY QISMLARI - Bekmurzaev, A.K.; Kulmurzaev, M.A. (SCIENCE and SOCIETY, 2022)
The article deals with the tasks of health-improving physical training, health improvement and strengthening, increasing the body resistance to the harmful effects of environmental factors and the effectiveness of the training process.
Keywords: health; training; sportmen; load; healthy life; indicators; stress; dynamics